A new species of Catolesia (Asteraceae, Eupatorieae) from Chapada Diamantina, Brazil - Roque, Nádia; Ferreira, Silvana C.; Amorim, Vivian O.; van Den Berg, Cássio (Phytotaxa, 2018)
Eupatorieae (Asteraceae) is the largest tribe of the Phytomelanic Fruit Clade, mostly restricted to the western hemisphere. Phylogenetic studies in Eupatorieae recovered some clades endemic to the Brazilian rocky fields. In one of these clades Catolesia is composed up to now by only two species, C. mentiens and C. huperzioides and it is distinguished by characters such as sessile leaves, capitulescence or heads surrounded by leafy-bracts, convex to conical, paleaceous receptacle, and pappus absent. In this study, we propose a new species of Catolesia, C. monocephala, characterized by the pedunculate and solitary capitula at the apex of the branches, aciculate leaf laminae, conical, paleaceous receptacle, paleae 60–70, spatulate, apex acute, and 60–100 flowers per head. The new species is endemic to the rocky fields vegetation from Esbarrancado mountain in the Mucugê and Palmeira municipalities, in Chapada Diamantina, Bahia, Brazil.